2013
DOI: 10.1177/1329878x1314800105
|View full text |Cite
|
Sign up to set email alerts
|

Still Not There: The Continued Invisibility of Female Athletes and Sports in the New Zealand Print Media

Abstract: This research examined parity for female athletes compared with male athletes in the level of coverage received in the New Zealand print media in a year that did not contain either the Commonwealth or Olympic Games. Using content analysis, 562 sport news articles from the New Zealand Herald and the Dominion Post were analysed. The findings revealed that female athletes received 6.1 per cent of coverage compared with male athletes, who received 73.6 per cent; articles related to female athletes/sports had an av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…However, it was evident that the female national game of netball (McLachlan, 2016;Pippos, 2017) was not a high priority in terms of story placement or news values, and there was a continued preference for men's sports such as rugby league, AFL, rugby union and cricket. These findings support Fink (2015) in that a major women's sport is not treated in the media in an equal -or even a comparable -way to men's sport, and contribute to coverage which can often be viewed as marginal or underrepresented (see Caple et al, 2011;French, 2013;Jones, 2005;Lumby et al, 2010;North, 2012;Sherry et al, 2016).…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…However, it was evident that the female national game of netball (McLachlan, 2016;Pippos, 2017) was not a high priority in terms of story placement or news values, and there was a continued preference for men's sports such as rugby league, AFL, rugby union and cricket. These findings support Fink (2015) in that a major women's sport is not treated in the media in an equal -or even a comparable -way to men's sport, and contribute to coverage which can often be viewed as marginal or underrepresented (see Caple et al, 2011;French, 2013;Jones, 2005;Lumby et al, 2010;North, 2012;Sherry et al, 2016).…”
Section: Discussionmentioning
confidence: 68%
“…Stories about the Super Netball season were covered predominantly like other sports, with a focus on tactics, analysis and injuries, and written almost always in a professional way. However, there remains a need for print newsrooms to pay greater attention to a sport that has such a large footprint across the country, especially with the broad reach of the media outlets' cross-platform publishing in newspaper and digital spaces, and the importance of print titles to society (French, 2013;Roy Morgan, 2018b;Watkins et al, 2017). This was a key conclusion from RQ1, with netball comprising less than 5% of total sports coverage during its peak season.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has consistently found that the volume of women’s sports media coverage is less than men’s sports (Bernstein, 2002; Cooky, Messner, & Musto, 2015; Fink, 2014; French, 2013; Godoy-Pressland, 2014). Media content analyses have offered crucial perspectives regarding the ways in which women’s sports are represented; however, content analysis alone offers little insight into the institutional structures that govern the process of news production from the viewpoint of those who produce it: journalists and editors.…”
Section: Literature Reviewmentioning
confidence: 99%